Answer :

Given,


f(x) =


Taking ‘a’ common from the first row


f(x) =


Applying C2 C1 + C2, we get-


f(x) =


Expanding about first R1 we get –


f(x) = a{(a+x)a – (-1)(ax+x2)}


f(x) = a{a2+ax + ax + x2}


f(x) = a(a2 + 2ax + x2) = a(a+x)2


f(2x) = a(a+2x)2


Hence,


f(2x) – f(x) = a(a+2x)2 – a(a+x)2


f(2x) - f(x) = a(a+2x-a-x)(a+2x+a+x) { a2-b2 = (a+b)(a-b)}


f(2x)-f(x) = ax(2a+3x)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers